Assistance and Training in Using Scrapbook Media Based on Picture and Picture Models Oriented to Nationalism at SDN Kedungsupit, Wonomerto District, Probolinggo Regency - Didit Yulian Kasdriyanto; Faridahtul Jannah; Berliana Emas Susilo; Fatimatus Zahro; Putri Oktaviani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Community service carried out to teachers and principals of SDN Kedungsupit, Wonomerto District, Probolinggo Regency in the form of training and assistance in using scrapbook learning media based on picture and picture learning models oriented to nationalism. The purpose of this service is to improve the understanding and skills of teachers in the use of scrapbook media based on picture and picture learning models oriented towards national insight to improve educational services and improve student learning processes and outcomes. The implementation method is in the form of activity planning, activity implementation, implementation techniques, monitoring and evaluation. The results and discussion of this service is an increase in enthusiasm in the process of understanding the use of scrapbook media based on picture and picture learning models oriented to nationalism so that it can improve educational services and processes and student learning outcomes at SDN Kedungsupit, Wonomerto District, Probolinggo Regency.